2017
DOI: 10.1371/journal.pone.0176849
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of cognitive-behavioral therapy in patients with bipolar disorder: A meta-analysis of randomized controlled trials

Abstract: BackgroundAlthough cognitive behavioral therapy (CBT) is considered a promising adjuvant to pharmacotherapy for treating bipolar disorder (BD), its efficacy is unproven. The present review and meta-analysis evaluated the treatment outcomes of patients with BD treated with CBT plus medication and compared these data with the outcomes of those who received standard care alone.MethodsElectronic searches from inception to July 31, 2016, were performed using PubMed, Medline OVID, Cochrane Library, EMBASE, CINAHL pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(86 citation statements)
references
References 46 publications
(63 reference statements)
1
76
0
5
Order By: Relevance
“…A meta‐analysis of 19 RCTs of cognitive behavioral therapy (CBT) in 1384 bipolar patients showed that CBT decreased relapse rate, decreased the severity of depression and mania, and improved psychosocial function . The analysis showed that CBT programs with sessions of 90 min or more are most effective, and the efficacy is more enhanced for bipolar I disorder than bipolar II disorder.…”
Section: Treatment Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta‐analysis of 19 RCTs of cognitive behavioral therapy (CBT) in 1384 bipolar patients showed that CBT decreased relapse rate, decreased the severity of depression and mania, and improved psychosocial function . The analysis showed that CBT programs with sessions of 90 min or more are most effective, and the efficacy is more enhanced for bipolar I disorder than bipolar II disorder.…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…242 A meta-analysis of 19 RCTs of cognitive behavioral therapy (CBT) in 1384 bipolar patients showed that CBT decreased relapse rate, decreased the severity of depression and mania, and improved psychosocial function. 243 The analysis showed that CBT programs with sessions of 90 min or more are most effective, and the efficacy is more enhanced for bipolar I disorder than bipolar II disorder. In the era of information technology, the efficacy of computerized CBT or smartphone-based activity monitoring 244 on treatment of BD is an issue that urgently requires study.…”
Section: Psychosocial Treatmentsmentioning
confidence: 99%
“…Results indicate that CBT could lower the relapse rate and improve manic and depressive symptoms, and psychosocial functioning, with a mild-to-moderate effect size. 93 Even though we could not find any paper focused on the treatment of comorbid PMDD/BD by means of psychotherapies, we can hypothesize their effectiveness as adjunctive treatments, based on their good proven efficacy on BD and PMDD separately, in accordance with Smith and Frey's recommendations. 47 Several research papers explored the effect of other treatments (ie, neither pharmacological nor psychotherapeutic approaches) on PMDD.…”
Section: Psychotherapy and Alternative Treatmentsmentioning
confidence: 69%
“…This diagnosis, which was made by the psychiatrist with over five years of clinical experience, was based on the ICD-10 classification system provided by the World Health Organization (WHO). Patients having bipolar disorder and exhibiting no signs of mania were included in the F3 group because a previous study has demonstrated that CBT is also effective in preventing the recurrence of bipolar depression in patients with bipolar disorder 10 .…”
Section: ② Inclusion Criteria For Gcbtmentioning
confidence: 99%
“…Furthermore, because there are no established criteria for GCBT, individual medical facilities create their own protocols and programs but the validity of such protocols and programs has not yet been verified. Although GCBT could be effective in treating not only major depressive disorder but also anxiety disorder and bipolar disorder (particularly, bipolar depression) 10 , no study has yet been conducted in Japan to evaluate the effectiveness of GCBT on psychiatric disorders other than major depression disorder.…”
Section: Introductionmentioning
confidence: 99%